2017
DOI: 10.1108/ijaim-03-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

The implication of information technology on the audit profession in developing country

Abstract: Purpose Information technology (IT) largely affected contemporary businesses, and accordingly, it imposes challenges on the auditing profession. Several studies investigated the impact of IT, in terms of the extent of use of IT audit techniques, but very studies are available on the perceived importance of the said issue in developing countries. This study aims to explore the impact of implementing IT on the auditing profession in a developing country, namely, Egypt. Design/methodology/approach This study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 33 publications
1
43
0
2
Order By: Relevance
“…BDA, as an IT tool, may also have a direct influence on compliance and substantive testing, as well as on evaluations and reports. Overall, the need to use BDA may depend on the requirements of the audit regulatory bodies and business clients, as well as on internal technological capabilities, IT-related managerial activities, such as the internal investments in hardware and software, external consultants and so on (Tarek et al, 2017).…”
Section: The Theoretical Frameworkmentioning
confidence: 99%
“…BDA, as an IT tool, may also have a direct influence on compliance and substantive testing, as well as on evaluations and reports. Overall, the need to use BDA may depend on the requirements of the audit regulatory bodies and business clients, as well as on internal technological capabilities, IT-related managerial activities, such as the internal investments in hardware and software, external consultants and so on (Tarek et al, 2017).…”
Section: The Theoretical Frameworkmentioning
confidence: 99%
“…The objectives study of (Tarek et al, 2017) are to explore the impact of implementing IT on the auditing profession in a developing country, namely, Egypt, examine auditors' perception on the extent of use and perceived importance of using technology in auditing in the different economic and cultural setting of Egypt. The findings of the study indicated that auditors' perception regarding client's IT complexity is significantly affected by the use of IT specialists and the IT expertise of the auditors.…”
Section: -Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Internal auditors need to possess IT skills to understand IT environments, in order to ensure the internal controls, and to ensure that new systems and modifications to existing systems are adequately performed to enable them to complete their audit work (Warren, 2004;Abu-Musa, 2008;Tarek et al, 2017).…”
Section: -5 Iiamentioning
confidence: 99%
“…The result indicated that there is a significant impact for e-commerce on auditing practices. Tarek et al (2017) examines the role of information technology on the Audit Profession in Developing Country. A questionnaire had been built and distributed to that study sample which consists of 112 auditors whom working at three of the Big 4 audit firms in Egypt.…”
Section: Literature Reviewmentioning
confidence: 99%